Prevalence and Associated Risk Factors of Immediate Postpartum Anemia in Two Teaching Hospitals in Mekelle: Northern Ethiopia - Fanta, Girma Abraham; zelelow, Yibrah Berhe (Ethiopian Journal of Reproductive Health, 2020)
Background: Anemia is a major global health problem this fundamental health issue still has not been solved and continues to exist affecting the health, quality of life, and working capacity in billions of people all over the world. It has been estimated that of the 500,000 maternal deaths occurring each year on a global scale in association with delivery, 20% are caused by peripartum hemorrhage and anemia. The frequency of postpartum anemia is poorly elucidated. The performance of postpartum hematocrit measurements after vaginal delivery to identify patients who are anemic is not practiced in our facility; so this research will help as to know the disease burden and also the most common associated factors. Objectives: Determine the prevalence and associated risk factors of immediate postpartum anemia in teaching hospitals, Northern Ethiopia. Methods: A facility based cross-sectional survey was employed in teaching hospitals in northern Ethiopia. A random sample of 236 postpartum women were included in the study. Socio-demographic and risk factors associated with postpartum anemia were collected by a standardized questionnaire. Blood samples were collected and processed using the standard procedures for hemoglobin determination. The samples were assessed for prevalence and associated factors for immediate postpartum anemia. A p-value <0.05 was considered significant in bivariate analysis. Variables which are found significant at bivariate analysis were analyzed by multivariate analysis. Then the final predictor was generalized by Odds ratio [OR] and 95% CI. Result: All 236 women participated in the study making the overall response rate 100%. Almost half 120 (50.8%) of the respondents are urban dwellers and 26(11%) were unable to read and write. The prevalence of immediate postpartum anemia in this study was 24.2%. There was significant association on multivariate analysis that the woman who came from rural areas are 66% less likely to develop postpartum anemia (AOR=0.34 and CI=0.118, 0.998); Mothers who are unable to read and write were 14.4 times more likely to have postpartum anemia (AOR=14.4 and 95% CI=2.27, 91.14); women who have estimated blood loss of less than 500 ml during delivery are 90.5% less likely to have postpartum anemia (AOR= 0.095 and CI=0.018,0.513);the mothers who deliver vaginally are 87% less likely to have immediate postpartum anemia (AOR=0.13 and CI=0.038, 0.454); mothers who are diagnosed to have PPH on clinical grounds were 7.4 times more likely to have immediate postpartum anemia (AOR=7.43 and CI=1.46, 37.79). Conclusion and recommendation: The results from this study shows that the prevalence of postpartum anemia is high and shows there is a significant number of women who have postpartum anemia after vaginal delivery which will be missed with the current protocol that we are using.